Sosialisasi Penemuan dan Pemasyarakatan Olahraga Rekreatif “Pancoair” dalam Rangka Meningkatkan Industri Wisata Air - Syahri Alhusin; Shodiq Hutmono (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2022)
Since the discovery of the Pancoair recreational sports design, quite a number of program activities have been carried out to develop and promote Pancoair. Among them are obtaining the Uberhaki Program from the Director General of Higher Education in 2001 to propose a Pancoair Patent, obtaining a MURI certificate in 2002, obtaining the Student Alternative Work Program in 2003, which was used to promote Pancoair throughout the districts of the former Surakarta Residency. In 2008 we held Pancoair performances and socialization in several swimming pools, including: at the Manahan Solo swimming pool, the Pengging Boyolali swimming pool, the Kartasuro Kopasus swimming pool, the Jolotundo Klaten swimming pool, and the Karanganyar swimming pool. In 2012, there were 300 Pancoair Seminars and Shows conducted by POK UTP students. In 2016-2019 the sport of Pancoair has been placed in the Muslim Oubond